The Influence of Technological Innovation and Employee Creativity on Organizational Performance at Misan University. - Mohammed Ahmed Waham; Reyath Thea Azeez Alsafo; Mohammed Raoof Al-Musawi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Today, higher education is one of the pillars of development and economic growth for every country in the world. The absence of innovation in higher education is one of the primary problems that Iraqi universities confront and still unable to overcome. This situation could be attributed to the dearth of strategic innovation programs and a lack of creativity in lecturing. Therefore, this study proposes a framework that fits innovation practices and employee creativity into the organizational performance of Misan University in Iraq. Quantitative methods were used to test the hypotheses and validate the fitness of the conceptual framework with the empirical data. Simple random sampling technique was used in the survey procedure. The study sample includes 500 lecturers, whereas 422 valid questionnaires have been included in the data analysis. The results show that innovation practices and creativity have a significant effect on the organizational performance of Misan University. These findings provide evidence that achieving superior performance in higher education no longer depends on the deployment of tangible assets like financial resources or the number of academic staff and faculty, but also on intangible assets such as creative lecturing and adopting innovation practices in the learning process. Thus, this study recommends that higher education institutions in Iraq focus on recruiting creative lecturers who can improve students' learning ability by promoting new ways of learning scientific materials in parallel with an innovation strategy in all organizational functions and processes.